Gestión Administrativa Y Su Incidencia En La Calidad Del Servicio A Los Usuarios De La Compañía De Transportes En Tricimotos 19 de mayo S.A Del Cantón La Maná, Provincia De Cotopaxi. Año 2020. - Lozada Lara, Natalia Abigail (2020)
This research aims to improve the administrative management of the Transport Company in “Tricimotos” 19 de Mayo S.A., from La Maná, for this purpose a manual of functions and administrative procedures of the company was designed to obtain real and reliable information, research techniques were used such as surveys conducted to managers, employees and users of the company which contribute to the diagnosis of the company and thus collaborate with the shortcomings such as: the lack of a structural-functional organization chart of the entity and inadequate administration. This research contributed significantly to the improvement of the development of the services offered by the company, since the manual contemplates the organizational structure, the adequate administrative process of the personnel. Companies must be characterized by the high level of quality of services offered to users who purchase their services, taking into account the consideration of the quality of them, this depends on the attitudes of staff. Quality is achieved through the entire process of service acquisition, operation and evaluation. All these results are acquired through instruments to evaluate the quality of services in the users, operating with a sample of 154 users to be surveyed.